Simulation of hybrid silicon nitride/polymer Mach-Zehnder optical modulator beyond 170 GHz - Huang, Beiju; Zhang, Zanyun; Li, Meixin; Zhang, Kaixin; Liu, Tianjun; Jiang, Hao; Wang, Qixin; Xing, Jiaming (Frontiers in Physics, 2022)
In this paper, a hybrid Mach-Zehnder optical modulator is proposed based on silicon nitride/organic polymer waveguides, which is expected to break through the performance bottleneck of the silicon-based optical modulator by exploiting the low-loss optical transmission property of silicon nitride waveguides and the excellent modulation performance of organic polymers. For reduction of the optical loss and ease of photonic packaging, perfectly vertical silicon nitride bidirectional grating couplers are utilized for both input/output optical coupling and power splitting/combining. Thus, a Mach-Zehnder interferometer can be constructed with a back-to-back configuration of such grating couplers. With grating apodization, the coupler can achieve a simulated coupling efficiency of 70%. To bridge the silicon nitride waveguides and the polymer waveguides, a longitudinal adiabatic mode-spot converter with a transmission efficiency of 99.2% was designed. In this paper, high-β donor-π bridge-accepter molecule YLD-124 combined with HD-BB-OH as the host polymer is utilized for a design example. The polymer waveguides with inverted ridge structure can be realized through the processes of silica cladding etching, spin coating or microfluidic trench filling of polymer. Following this design, we numerically demonstrate a hybrid silicon nitride-polymer Mach-Zehnder modulator with modulation efficiency of 1.57 V·cm and Electric-Optical bandwidth of 174 GHz. The total insertion loss is less than 5.74 dB, including two grating coupler losses of about 3.08 dB.